2014
DOI: 10.1371/journal.pone.0115396
|View full text |Cite
|
Sign up to set email alerts
|

Relating Specific Emotions to Intrinsic Motivation: On the Moderating Role of Positive and Negative Emotion Differentiation

Abstract: Despite the fact that studies on self-determination theory have traditionally disregarded the explicit role of emotions in the motivation eliciting process, research attention for the affective antecedents of motivation is growing. We add to this emerging research field by testing the moderating role of emotion differentiation –individual differences in the extent to which people can differentiate between specific emotions– on the relationship between twelve specific emotions and intrinsic motivation. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…In supporting this view, the mediation role of emotional intelligence in the relationship between personal traits and positive resources predicting individual well-being has recently been observed [42]. Moreover, the finding that emotional intelligence is related to the need for relatedness factor of SDT adds new light on the relationship between motivational systems and emotional intelligence [66,67].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In supporting this view, the mediation role of emotional intelligence in the relationship between personal traits and positive resources predicting individual well-being has recently been observed [42]. Moreover, the finding that emotional intelligence is related to the need for relatedness factor of SDT adds new light on the relationship between motivational systems and emotional intelligence [66,67].…”
Section: Discussionmentioning
confidence: 91%
“…According to the SDT, psychological needs contain both cognitive and affective components and the need for relatedness appears as an important motivation factor for the development of emotional intelligence [25]. Moreover, it has been observed that the capability in managing with emotions is associated with the emotion-intrinsic motivation relationship [66]. More recently, Watson and Kleinert [67] showed that coaches' emotional intelligence is related to basic need satisfaction in athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Emotions help humans to adapt themselves to problems and challenges they face; almost all new theories that have been put forward in the field of emotions emphasize the positive and adaptive role of emotions in humans' behavior. Many other studies also emphasize the undeniable role of emotions in different processes of the mind such as decision making and processing of information (31).…”
Section: Discussionmentioning
confidence: 99%
“…Different models have been proposed about which appraisals contribute to which emotions, and the intricate relationships between motivation and emotion are yet to be fully uncovered in psychology (e.g., [92]). One clear connection is offered by Lazarus [42]: In his structural model of appraisal, so called primary appraisals comprise evaluations of motivational relevance and motivational congruence.…”
Section: From Motivation To Emotionmentioning
confidence: 99%